Repositioning Emotional Wellbeing as a Core Pillar of Educational Policy: A Narrative Review - Lestari, Putri Ayu; Safitri, Awalina Dea (Sinergi International Journal of Education, 2025)
Emotional wellbeing in the classroom has become an increasingly critical issue in contemporary educational policy. This narrative review investigates the role of curriculum-based interventions, teacher capacity, and school environment in promoting students' emotional wellbeing, drawing from global and interdisciplinary literature. Employing a structured narrative methodology, this review synthesizes evidence from empirical studies across developed and developing contexts, focusing on Social-Emotional Learning (SEL) frameworks and policy responses. The results demonstrate that integrated SEL programs significantly enhance students’ emotional regulation, reduce anxiety, and foster a supportive classroom climate. Effective implementation depends not only on curriculum design but also on teacher training, institutional commitment, and policy coherence. The discussion reveals systemic barriers, including resource limitations and cultural misalignment, which hinder sustainability. Comparative insights highlight that while developed countries benefit from structured national strategies and digital tools, developing contexts often rely on community-based, adaptive models. This study advocates for flexible policy design, intersectoral collaboration, and investment in teacher wellbeing as key strategies to improve intervention outcomes. Additionally, digital innovation and participatory policy development are recommended to bridge implementation gaps. The findings underscore the urgency of elevating emotional wellbeing within education systems and call for further longitudinal research on sustainable, context-responsive SEL initiatives.